Russia's rising military and communication power: From Chechnya to Crimea. (June 2023) - Rodgers, James; Lanoszka, Alexander
Most scholars working on Russia's use of strategic narratives recognize the importance of the Russian state. Nevertheless, the authors argue that much of the attention on strategic narratives has given insufficient appreciation for how Russia has developed its military and media policies in a coordinated manner: learning from its mistakes and failures as it went along, and becoming more efficient each time. In making their case, they examine three theatres of Russian military activity and their accompanying media coverage: the wars in Chechnya in 1994–1995 and 1999–2000; war with Georgia in 2008 over the separatist territories of South Ossetia and Abkhazia; and Ukraine, especially Crimea, since 2014. The Russian leadership addressed the shortcomings on each occasion, with the news media being increasingly weaponized as time went on. The authors argue that scholars should see Russia's evolving uses of those military and media power resources as part of a single strategic process. How the Russian state goes about its media policy can accentuate the military intervention for better or for worse as far as its image is concerned.